1998
DOI: 10.1177/10454411980090030301
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Non-Immune Host Cells and the Immune System During Periodontal Disease: Role of the Gingival Keratinocyte

Abstract: Periodontal disease and inflammatory dermatoses, such as psoriasis, are characterized by the accumulation of dense inflammatory infiltrates immediately beneath the epithelial cell layer of the gingiva and skin, respectively. Dermatologists are increasingly aware that the epidermal keratinocyte probably contributes to inflammatory disease progression by secreting a number of pro-inflammatory cytokines and expressing various adhesion molecules. In psoriatic lesions, it is now believed that epidermal keratinocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 150 publications
(121 reference statements)
0
36
0
Order By: Relevance
“…The inflamed site is characterized by an infiltration of neutrophils. Infiltration of neutrophils into gingival tissues is an early event in gingival inflammation, and neutrophils are the predominant leukocytes in the gingival crevicular fluid (GCF) (ϳ90%) (48). It is also evident that GCF has neutrophil serine proteinase activities against MeOSuc-Ala-Ala-Pro-Val-pnitroanilide for HLE and Suc-Ala-Ala-Pro-Phe-p-nitroanilide for Cat G (49).…”
Section: Discussionmentioning
confidence: 99%
“…The inflamed site is characterized by an infiltration of neutrophils. Infiltration of neutrophils into gingival tissues is an early event in gingival inflammation, and neutrophils are the predominant leukocytes in the gingival crevicular fluid (GCF) (ϳ90%) (48). It is also evident that GCF has neutrophil serine proteinase activities against MeOSuc-Ala-Ala-Pro-Val-pnitroanilide for HLE and Suc-Ala-Ala-Pro-Phe-p-nitroanilide for Cat G (49).…”
Section: Discussionmentioning
confidence: 99%
“…51,52 Although a role for keratinocytes in the immunoregulation of periodontal disease has been proposed, the specific functions of cell surface receptors and their ligands, such as ␣v␤6 integrin and TGF-␤1, have not yet been investigated. 53 It is possible that keratinocytes serve as nonprofessional, antigen-presenting cells to the underlying lymphocytes in a process that is regulated by TGF-␤1. In addition, keratinocytes may inhibit the proliferation of unprimed T cells via a TGF-␤1-mediated mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…IL-8 secreted by gingival epithelial cells might act as a chemo-attractant for neutrophils and T cells [29,30]. These accumulated cells might express LFA-1 on their cell surface and attach to epithelial cells via ICAM-1 and LFA-1 interaction, then in®ltrate into the gingival epithelium [8,27]. In fact, ICAM-1 and IL-8 mRNA expression are topographically associated with the area of neutrophil migration in the junctional epithelium [31].…”
Section: Mrna Expression For Il-8 G-csf Gm-csf and Icam-1 By Gingivmentioning
confidence: 99%
“…The ®rst cells encountered by bacteria are epithelial cells, and the predominant cell type in the gingival epithelium is the keratinocyte [8]. Skin keratinocytes and keratinocytic cell lines produce various cytokines and growth factors [9] and some studies [10,11] have also shown cytokine production by human oral keratinocytes and related cell lines in response to stimulation with oral bacteria.…”
Section: Introductionmentioning
confidence: 99%